Green tea extract–modified silica gel decorated with palladium nanoparticles as a heterogeneous and recyclable nanocatalyst for Buchwald-Hartwig C–N cross-coupling reactions. (March 2020) - Veisi, Hojat; Tamoradi, Taiebeh; Karmakar, Bikash; Hemmati, Saba
Abstract: A novel green tea extract–encapsulated silica gel decorated with in situ–generated Pd nanoparticles is reported as an efficient, green heterogeneous catalyst in the Buchwald-Hartwig C–N cross-coupling reaction. It was characterized by several analytical techniques. Thereafter, a wide range of aryl amines were synthesized in good to excellent yields by reaction of different substituted aryl halides and secondary amines over the catalyst. The material is sufficiently stable and could be used at least six times in a model Buchwald-Hartwig reaction without noticeable change in its catalytic activity. Heterogeneity of the catalyst was examined by a hot filtration test. Graphical abstract: Image 1 Highlights: In situ–generated palladium nanoparticles anchored to green tea extract–coated silica gel. Excellent performance as a reusable catalyst in Buchwald-Hartwig C–N cross-coupling reactions. Excellent yield of the products. Catalyst used up to six times.